Gender and Corruption: The Neglected Role of Culture - Julia Debski; Michael Jetter; Saskia Mösle; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2016)
Empirical findings of a negative association between female participation in politics and the labor market, and levels of corruption have received great attention. We reproduce this correlation for 177 countries from 1998 to 2014. Once taking account of country-specific heterogeneity by fixed effects, the negative association disappears entirely in terms of statistical significance and magnitude. This suggests that female participation in politics and the labor market is not directly linked to lower corruption. Exploiting different dimensions of culture as country-specific characteristics, our analysis shows that power distance and masculinity systematically affect corruption. These two cultural characteristics are sufficient to fully mitigate any association between gender and corruption. Our findings point out the importance of culture and suggest that its omission causes a spurious correlation, leading to the erroneous claim that increased female participation in public life alone reduces corruption.
Keywords: J16; D73; Z10; 330; Gender; corruption; female participation; power distance; culture; development